Análise quali-qualitativa e por meio de sistema de informações geográficas da arborização do quadrilátero central de Ribeirão Preto, SP - Romani, Gustavo de Nobrega [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Vegetation in urban environments is essential as a city quality element, and its proper maintenance reduces disturbances caused by building trade excesses, which removes native woods, changing local microclimate other than flora and fauna biological cycle alterations. Quantitative and qualitative survey of arboreal specimens of cities provides useful data for decision making of afforestation master plans, helping to improve urban environment citizen benefit. Ribeirão Preto city downtown holds great historical and cultural importance, since it was where the city began to grow. In this way, we aimed to conduct a phytosociological and quali-quantitative survey of trees and palms along the streets; and through Landsat TM local maps, detect vegetation growth or decline over the years, and observing possible heat island formations through temperature map analysis. Total tree and palm individuals were 1832 split into 89 species, 72 genera and 35 botanical families. Although the area presents high species diversity, verified by Shannon-Weaver index (3.41), most species are not Brazil-native, in small and medium heights. We observed that the major afforestation problems were related to inadequate pruning, poorly dimensioned planting holes and excessive spacing between plants. There was an average 70% reduction of NDVI of most squares between 1984 and 2011, except for Bandeiras that had 64.29% increase of it. Average temperature in squares was about 1 to 2 °C lower than in the surrounding area until 150-200 meters far. Digital Elevation Model (DEM) can be used in forward square planning of neighborhoods, identifying appropriate locations to set squares, parks and green areas in order to improve water infiltration into the soil without overloading storm drainage system. Although diverse, the afforestation on the central quadrangle needs attention, especially for problems related to tree and palm ...

A vegetação no ambiente urbano consiste em um importante fator de qualidade para uma cidade e mantê-la de forma adequada nos centros urbanos reduz transtornos causados pelos excessos da construção civil que, ao retirar a vegetação original, altera o microclima local além de causar transtornos aos ciclos biológicos da fauna e flora. A avaliação quantitativa e qualitativa dos exemplares arbóreos presentes nas cidades fornece dados para a tomada de decisão de planos diretores de arborização urbana dos municípios, ajudando na melhoria do ambiente em favor dos próprios cidadãos. O quadrilátero central de Ribeirão Preto (SP) tem grande valor histórico-cultural para o município, pois foi desta área que se iniciou o crescimento da cidade. Desta forma, objetivou-se fazer o levantamento fitossociológico e quali-quantitativo das árvores e palmeiras encontradas nas vias públicas do quadrilátero central de Ribeirão Preto (SP) e por meio de mapas Landsat TM detectar o crescimento ou diminuição da arborização ao longo dos anos, observando possíveis ilhas de calor pela análise de mapas de temperatura. O total de exemplares arbóreos e palmeiras foram de 1.832 indivíduos, pertencentes a 89 espécies, 72 gêneros e 35 famílias botânicas. Embora o local apresente arborização com boa diversidade de espécies, verificada pelo índice de Shannon-Weaver (3,37), a maior parte das espécies encontradas não é endêmica do Brasil, e são de pequeno e médio porte. Foi observado que os maiores problemas com relação ao projeto da arborização foram podas inadequadas, covas mal dimensionadas e excessivo espaçamento entre plantas. Entre os anos de 1984 a 2011 houve uma redução média de 70% no índice de vegetação das praças, exceto para a Praça das Bandeiras, que teve um aumento de 64,29%. A temperatura média no centro das praças é cerca de 1 a 2 °C menor do que em região ...
Keywords: Arvores; Comunidades vegetais; Ilha de calor urbana; Arborização das cidades; Vegetação - Mapeamento; Vegetation and climate